Inclusion of human rights in sexual and reproductive health programming: Facilitators and barriers to implementation. Issue 10 (3rd October 2021) - Gruskin, Sofia; Zacharias, Kristin; Jardell, William; Ferguson, Laura; Khosla, Rajat
ABSTRACT: The need to prioritise those furthest behind is well understood in global health circles, and how human rights norms and standards can help often touted. As rights concerns are particularly recognised in sexual and reproductive health (SRH) programming, as part of a larger exercise, a review was conducted to identify documented barriers and facilitators to implementation. Given the role global guidance plays in implementing rights-based approaches to SRH, UNDP/UNFPA/UNICEF/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction (HRP) guidelines, tools, recommendations and guidance that include the explicit mention of human rights principles served as the basis for this exercise. This was followed by an extensive review of the literature. Sources reviewed confirmed barriers include not only broad structural, policy and health systems barriers but financial, staffing and time constraints, as well as lack of understanding of concretely how to include human rights in these efforts. Facilitators include the existence of human rights champions, leadership, strong civil society participation, training, and funding made available specifically for implementation. Investment in indicators and documentation sensitive to human rights is warranted in sexual and reproductive health, as well as other health topics, to best serve populations who need them most.